Governing Conjugality: Social Hygiene and The Doctrine of Restitution of Conjugal Rights in England and India in the Nineteenth Century. Issue 1 (2nd January 2021) - Lammasniemi, Laura; Sharma, Kanika
Abstract: This article focuses on the doctrine of restitution of conjugal rights (RCR) as a colonial legal transplant and examines how ideas of social and moral hygiene manifested in the debates around the doctrine in late-nineteenth century England and India. Originating in ecclesiastical law, the doctrine of RCR provides remedies and sanctions for the deserted spouse when one party has violated the obligation to cohabit as husband and wife. Through a critical examination of the history and application of the doctrine, the article traces the specific ways in which such suits developed and became rooted in Hindu, Parsi and Muslim marital law in India, while simultaneously falling out of favour in England. It places the doctrine in the context of changing ideas of marriage and argues that social hygiene became the tool through which the doctrine was both resisted in England and lauded in colonial India.